Diagnóstico ambiental da APP e da área inundável do rio Paranaíba em Patos de Minas/MG e diretrizes para recuperação - Amaral, Eni Aparecida do (2018)
Modifications in environmental preservation areas are often influenced or potentiated by anthropic action mainly because of unplanned urbanization process and intensive agricultural and pasture practices, which in turn cause deforestation, degradation and irregular land uses. This study aimed to carry out an environmental diagnosis of the Paranaiba River’s Permanent Preservation Area and floodplain in its urban stretch located in Patos de Minas/MG. For this, digital classification methods (maximum likelihood and segmentation of NDVI values) were carried out in order to determine the native vegetal coverage and land use in the area defined as Permanent Preservation Area, according to the parameters of the Brazilian Forest Code and in the flood-prone area declared as permanent preservation at the municipal level (area bounded by the altimeter elevation of 782 meters). Moreover, the main environmental impacts were identified, and then, they were analyzed through the adapted matrix from Leopold (1971). For survey of impacts, only the APP area with limits established by Forest Code were considered. The classification by maximum likelihood obtained better Kappa index (0,84) and showed riparian forest in 34,01% of the floodable area. Pasture was the predominant class in the entire floodplain of the river (39,52 %). The remain area (26,47%) was represented by water, buildings, exposed soil and Eucalyptus sp. As far as the Permanent Preservation Area, with limits defined by the Forest Code is concerned, vegetation remnants occupied most of the area (56,62%), while remaining areas (43,38%) was occupied by other uses, pasture predominantly. The main negative impacts, of anthropogenic origin, identified in the Paranaíba River's permanent preservation area were: disposal of solid waste, presence of cattle and horses, presence of exotic or invasive species, release of domestic and industrial effluents, absence or inefficiency of energy sinks, erosion and deposition of sediments within the river, internal trails, fisheries, and slabs and fires. The joint analysis of the coverage and land use classes, together with the survey and evaluation of environmental impacts, allowed to identify the areas in conflict with environmental legislation, and still degraded and / or with irregular uses, indicating regularization and recovery needs.